2004
DOI: 10.1152/ajpendo.00477.2003
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of angiotensin II type 2 receptor expression in estrogen-induced pituitary hyperplasia

Abstract: Recent evidence shows that reexpression and upregulation of angiotensin II (ANG II) type 2 (AT2) receptor in adult tissues occur during pathological conditions such as tissue hyperplasia, inflammation, and remodeling. In particular, expression of functional AT2 receptors in the pituitary and their physiological significance and regulation have not been described. In this study, we demonstrate that chronic in vivo estrogen treatment, which induces pituitary hyperplasia, enhances local AT2 expression (measured b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 56 publications
1
10
0
Order By: Relevance
“…Progesterone effects on adrenal AT 2 receptors have not been studied. However, in the pituitary gland, progesterone does not alter the AT 2 receptor expression induced after estrogen-induced hyperplasia [40]. AT 2 receptor upregulation may also be a response to the high estrogen levels during our experiments, above those occurring during the estrous cycle but similar to those found during pregnancy.…”
Section: Discussionmentioning
confidence: 53%
“…Progesterone effects on adrenal AT 2 receptors have not been studied. However, in the pituitary gland, progesterone does not alter the AT 2 receptor expression induced after estrogen-induced hyperplasia [40]. AT 2 receptor upregulation may also be a response to the high estrogen levels during our experiments, above those occurring during the estrous cycle but similar to those found during pregnancy.…”
Section: Discussionmentioning
confidence: 53%
“…Intracellular Ca 2+ was performed as previously described using Fura-2/AM (tetracetoxymethylesther-Fura 2) as a fluorescent indicator Suarez et al, 2004). Briefly, adenohypophyseal cells were incubated for 30 min in a buffered saline solution (BSS: 140 mM NaCl, 3.9 mM KCl, 0.7 mM KH 2 PO 4 , 0.5 mM Na 2 HPO 4 ·12H 2 O, 1 mM CaCl 2 , 0.5 mM MgCl 2 , 20 mM Hepes, pH 7.5) in the presence of FURA-2/ AM 1.5 μM, 10 mM glucose, 0.1% BSA.…”
Section: Intracellular Ca 2+ Measurementsmentioning
confidence: 99%
“…Furthermore estrogen treatment produces involution of somatotrophs and gonadotropin-producing cells (De Nicola et al, 1978). In addition, it has been shown that estrogens alter the sensitivity of adenohypophyseal cells to stimulatory and inhibitory factors, such as dopamine, TRH, angiotensin II and GABA (Apud et al, 1985;Diaz-Torga et al, 1998;Livingstone et al, 1998;Suarez et al, 2003Suarez et al, , 2004. Moreover, ovarian steroid hormones modulate GABAergic neurotransmission in various brain areas by altering GABA A R function or subunit composition (Herbison and Fenelon, 1995;Schumacher et al, 1989;Weiland and Orchinik, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the release of ang II from hypothalamus has been described to rise in response to estrogen [24]. Next, a chronic exposition to DES led to the upregulation of the AT2 receptor gene transcription and increase in the functional AT2 receptor expression in anterior pituitary of rats [25]. …”
Section: Introductionmentioning
confidence: 99%